Benthic shear stress and sediment condition - Peterson, Eric L. (Aquacultural engineering, 1999)
This article presents a literature review and analysis which finds that the conditions in a shallow waterway are dependent on the underlying shear stress. Circulation and mixing have been recognised as somehow important to the health of the lower water column and sediment of a pond. Benthic shear stress is identified as one of the principal governors of sediment condition. Benthic shear stress regulates the convection of volatile substances such as oxygen across the sediment–water interface. Benthic shear stress is the primary determinant of where particulate matter scours, rolls, saltates, settles, and consolidates. The critical shear stress of very small particles tends to be determined by density rather than size. Excessive shear stress may cause organic material to become buried under a fallout of silt in locations with lower shear stress. Such organic matter trapped in a sludge blanket consumes oxygen faster than it can diffuse through the pores between grains of soil, resulting in anaerobic soils. The objective of pond aeration and circulation systems should be to optimise conditions for the growth of cultured stock. Better management of the epi-benthic habitat of shrimp and prawns would concurrently reduce the use of energy and soil. The finding is that pond sediment condition may be assessed in terms of benthic shear stress. Control of benthic shear stress would enable resuspension and oxygenation of organic detritus without making the situation worse by intermixing organic matter with mineral soil. Desirable benthic shear stresses are expected to exist in the range of 0.003–0.03 N/m 2 where organic matter is gently maintained in an aerobic state. Locations having less than 0.001 N/m 2 benthic shear stress are subject to burial under accumulating mineral silts. Excessive scour occurs in locations having more than 0.1 N/m 2. High stress locations are the source of suspended solids which fallout on locations experiencing lower rates of benthic shear stress. The declining productivity of shrimp mariculture ponds is associated with excessive stocking and feeding because these practices necessitate intensive aeration, which results in high rates of pond circulation. The circulation causes soil to be scoured in some places while fallout covers the bottom in other places. Consequently intensive cropping of a pond causes feed pellets and other organic material to be buried in the soil, creating anaerobic conditions whereby bacterial metabolites are produced and released into the water column.